SLANG WORDS USED IN YOUTUBE VIDEO JOJI JUDGES A BOBA TEA BATTLE BETWEEN RICH BRIAN AND NIKI: A SOCIOLINGUISTIC STUDY - Trya Indah Lestari; Felesya Hijrian Alfatihah; Nurul Athalla Rania; Gracesila Hanna Caroline Turnip; Gaguk Rudianto (Fakultas Ilmu Budaya Universitas 17 Agustus 1945 Surabaya, 2022)
This research aimed to analyze the slang words found in the YouTube video Joji Judges a Boba Tea Battle between Rich Brian and Niki. To find out the types of slang used by participants in the video. This descriptive qualitative research focused on the types of slang words in this video according to Alan and Burridge theories. Method of collecting data by the observation in the observational method with non-participatory technique. In analyzing the data, this research used the method of free listening and take note technique proposed by Sudaryanto. From this research, the results showed that there were 30 data of slang: 2 slang terms in flippant such as I was like ready to rip on it, 4 slang terms in clipping, 4 slang words in imitative, and 20 slang words in fresh and creative, and there are no slang words in the acronym. Based on the results, it can be concluded that the most widely used slang type is the acronym form and the least flippant.